CLINICAL CASE OF RARE TYPE V OSTEOGENESIS IMPERFECTA - G. T. Yakhyayeva; T. V. Margieva; L. S. Namazova-Baranova; K. V. Savostyanov; A. A. Pushkov; N. V. Zhurkova; K. V. Zherdev; N. D. Vashakmadze; A. K. Gevorkyan (Union of pediatricians of Russia, 2015)
Osteogenesis imperfecta, also known as the brittle bone disease, is a clinically heterogenic hereditary connective tissue disease characterized by brittle bones and high risk of skeletal bone fractures. Other observable symptoms, such as deformities of limb and spinal bones, blue sclerae, dentinogenesis imperfecta and progressive hearing loss vary in severity depending on the type of the disease. According to the original classification by D.O. Silence (1979), there are 4 types of osteogenesis imperfecta; however, the number thereof has multiplied due to discovery of new disease-inducing mutations. Type V osteogenesis imperfecta is distinguished by characteristic clinical radiographic symptoms; also, patients with this type of the disease do not feature a type I collagen gene mutation. Nevertheless, all types of osteogenesis imperfecta, including type V, are characterized by high bone brittleness, frequent fractures and further bone deformities, which is the most common cause of incapacitation of the patients.